Pengaruh kadar tambang (Cu) terhadap sifat mekanis aluminium matrix composite berpenguat alumina dibuat secara ekstruksi - Subarmono, Subarmono; Pardadi, Janu (2011)
The objective of this research is to find effect of copper on the mechanical properties of aluminium matrix composite (AMC), which is reinforced by alumina and made using hot extrusion. The amount of copper of 1;3 and 5wt% and 10wt% local alumina were added to the aluminium fine powder as matrix. Each was mixed using rotary mixer for 2hr. The mixture was then uniaxially compacted with a pressure 100 MPa to produce green body. The green body was then extruded at 600°C and ratio 4/9. Each composites was tested of bending strength, porosity. hardness and wear rate. From the data testing can be found effect of copper on the mechanical properties of AMC. The results show that mechanical properties decrease with inceasine of fraction of copper. The best mechanical properties such as bending strength, porosity, hardness and wear rate is on the AMC with 1wt% copper, there are 387 MPa, 0,5%, 80 VHN and 0,013 mg/MPa.m, respectively